Pemikiran Pendidikan Multikultural Ki Hadjar Dewantara - Muthoifin Muthoifin (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
Ki Hadjar’s thought about multicultural education is Pancadarma (five principles). While the pattern his educational thought is nationalistic and universal. Nationalistic, because of the education based and source on the principle of national culture. While universal, Ki Hadjar want education to be received and enjoyed by a variety of groups, race, tribe, nation, and religion. The essence of teaching is focused on teaching character (characters), human (humanism), liberty (freedom), and national culture (multicultural).